2022
DOI: 10.1021/acs.langmuir.2c01938
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-Loaded Copper Peroxide Nanoparticles with Redox Balance Disrupting Capacity for Enhanced Chemodynamic Therapy against Tumor Cells

Abstract: Chemodynamic therapy (CDT) is a promising hydroxyl radical (•OH)-mediated tumor therapeutic method with desirable tumor specificity and minimal side effects. However, the efficiency of CDT is restricted by the pH condition, insufficient H2O2 level, and overexpressed reductive glutathione (GSH), making it challenging to solve these problems simultaneously to improve the efficacy of CDT. Herein, a kind of polyvinylpyrrolidone-stabilized, sorafenib-loaded copper peroxide (CuO2-PVP-SRF) nanoparticle (NPs) was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…49,50 A PVP-stabilized sorafenib-loaded copper peroxide (CuO 2 ) nanoparticle was fabricated to induce lipid hydroperoxide accumulation-induced ferroptosis. 51 The • OH generated by CDT may be eliminated to decrease the therapy effects on the performance of reduced glutathione (GSH). 52,53 Some studies have shown that metal ions can enhance CDT effects by depleting GSH to develop antitumor capacity.…”
Section: Introductionmentioning
confidence: 99%
“…49,50 A PVP-stabilized sorafenib-loaded copper peroxide (CuO 2 ) nanoparticle was fabricated to induce lipid hydroperoxide accumulation-induced ferroptosis. 51 The • OH generated by CDT may be eliminated to decrease the therapy effects on the performance of reduced glutathione (GSH). 52,53 Some studies have shown that metal ions can enhance CDT effects by depleting GSH to develop antitumor capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Copper ion is widely used in CDT since Cu + can participate in Fenton-like reaction to generate ·OH (Qiu et al., 2022 ; Chen et al., 2022 ; Wang et al., 2022 ). At the same time, it was also reported that Cu 2+ can mediate effective loading of DOX, which is based on the complexation of drugs with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemodynamic therapy (CDT) has been recognized as a promising tumor therapeutic method. The principle is using specific valence metal ions (such as iron ions, manganese ions, etc.) to react with endogenous high-concentration hydrogen peroxide (H 2 O 2 ) in tumor tissues to produce strong oxidizing hydroxyl radicals ( • OH) for tumor cell killing. , However, the reaction conditions always limit the therapeutic effect of CDT. , It has been reported that the efficacy of the Fenton reaction can be promoted at the elevated temperature condition. The photothermal effect leads to an increase in the temperature of tumor tissue, which can accelerate the production of • OH.…”
Section: Introductionmentioning
confidence: 99%
“…6,35 However, the reaction conditions always limit the therapeutic effect of CDT. 33,36 It has been reported that the efficacy of the Fenton reaction can be promoted at the elevated temperature condition. The photothermal effect leads to an increase in the temperature of tumor tissue, 37−40 which can accelerate the production of • OH.…”
Section: ■ Introductionmentioning
confidence: 99%